2020
DOI: 10.4081/idr.2020.8736
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Photodynamic Inactivation with Laser Diode on Staphylococcus aureus Biofilm with Various Ages of Biofilm

Abstract: Biofilms are able to casue microorganisms to be 80% more resistant to antibiotics. The extracelullar polymeric substance (EPS) in biofilm functions to protect bacteria, making it difficult for antibiotics to penetrate the biofilm layer. This study aims to determine the effective- ness of photodynamic inactivation with blue diode laser to reduce Staphylococcus aureus biofilm at various ages of biofilms. The light source is a 403 nm blue diode laser with an energy power of about 27.65±0.01 mW. The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
(67 reference statements)
0
6
0
Order By: Relevance
“…Diode laser irradiation was carried out with variations in the length of the irradiation time of 30, 60, 90, 120, 150, and 180 seconds. The energy density value can be calculated using equation 1 9 :…”
Section: Light Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…Diode laser irradiation was carried out with variations in the length of the irradiation time of 30, 60, 90, 120, 150, and 180 seconds. The energy density value can be calculated using equation 1 9 :…”
Section: Light Sourcementioning
confidence: 99%
“…Photodynamic inactivation (PDI) is a method of inactivating microorganisms by utilizing light to activate a photosensitizer (PS) agent that produces reactive oxygen species (ROS), causing cell lysis. 7,8 The suitability of the light spectrum with the PS absorption spectrum is the key to photophysical reactions, namely the absorption of light energy by PS agents, which will trigger photochemical and photobiological reactions to produce antimicrobial effects 9,10 and biomodulation. 11 PS is a light-sensitive molecule that plays a role in absorbing light energy.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have been reported that aPDT-generated ROS has many possible targets on biofilms, mainly against EPS matrix [ 99 ] that includes the DNA [ 100 ], lipids [ 101 ], proteins [ 102 , 103 ] and extracellular polysaccharides [ 104 ]. In addition [ 105 ], showed the efficacy of the aPDT against several stages of biofilm development. Thus, they designed experiments to analyze the effect of different light doses (4.23; 8.46; 12.70; 16.93 and 21.16 J/cm 2 ) against several ages of S. aureus biofilms (0; 6; 11; 17; 24; 32; 40 and 48 hours).…”
Section: Bio-effects Of Apdt and Pefmentioning
confidence: 99%
“…The larger the photon intensity and the longer the exposure, the more photosensitizer will be activated to produce various ROS that has an effect on the number of bacterial deaths. 24 One of the most common and frequently used root canal irrigation agents to date is 2.5% NaOCl. Bacteria can penetrate the root dentinal tubules to a depth of 1000 µm, while the irrigation disinfection material only reaches a depth of 100 µm.…”
Section: Introductionmentioning
confidence: 99%